Physical Manifestation of Death in Macbeth - Andrejević, Ana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
Murders, wars, blood, severed heads, natural disasters, but also supernatural phenomena such as ghosts, witches, and prophecies dominate Shakespeare`s tragedy Macbeth. If we consider the abundance of images of darkness, fear, and nightmares too, it is difficult to resist the impression that the apocalyptic threat is over Scotland and implicitly over the whole world if it is ruled by a tyrant’s hand. Death as a phenomenon is omnipresent in Macbeth: physically and metaphysically, realistically and symbolically, explicitly and implicitly. The author of this paper will focus more on those explicit and physical images of death than on metaphysical ones, in order to emphasize their importance in creating the atmosphere of destruction and hell in this tragedy. The paper will attempt to discover the purpose of these images in the tragic course of the action, since the mere accumulation of the terrible scenes of death is a characteristic dramatic convention for melodramas, which Macbeth certainly is not. On the contrary, the diverse macabre images of death in Macbeth are in the function of the tragic pathos and the characterization of the protagonists.